The Effect of Qiroati and Non Qiroati Methods in Improving Students' Ability to Read and Write the Qur'an at TPQ Al-Ikhlas - Nazih Sadatul Kahfi; Raharjo Raharjo; Ikhrom Ikhrom (Journal on Education, 2024)
This study aims to determine the ability to read the Qur'an and find out how much influence the Qira'ati and Non Qiroati methods have in improving the ability to read the Qur'an in TPQ Al-Ikhlas students. The results of this study indicate that: 1.) The Qiro'ati method at TPQ Al-Ikhlas is included in the “good enough” category, namely with an average of 47.2. 2.) The ability to read the Qur'an at TPQ Al-Ikhlas is in the “good enough” category, namely with an average of 77.2. 3.) The effect of the qiro'ati method on the ability to read the Qur'an at TPQ Al-Ikhlas students has a “Moderate” correlation. This is evidenced by the correlation test results of 0.502 which lies in the degree of value of 0.40 to 0.599 (moderate correlation). Then, in the significance test results, obtained a result of 3.071 which is greater than the t table of 2.032. Because tcount> ttable, the results of these calculations indicate the influence of the qiro'ati method on the ability to read the Qur'an in TPQ Al-Ikhlas students. That is, if the Qiro'ati method is used more in the process of learning the Qur'an at TPQ Al-Ikhlas, it can affect students' ability to read the Qur'an. As much as 25% of the influence of this method consists of other factors, such as internal and external factors, which can affect students' ability to read the Qur'an.